Optical imaging of the propagation patterns of neural responses in the rat sensory cortex: Comparison under two different anesthetic conditions. (22nd January 2015) - Hama, N.; Ito, S.-I.; Hirota, A.
Highlights: We recorded neural activities in the rat cerebral cortex by multiple-site optical recording. We compared spatio-temporal patterns under different anesthetic conditions. Both the propagation velocity and the full width at half maximum differed. Neither the amplitude nor the slope of the rising phase differed. Abstract: Although many studies have reported the influence of anesthetics on the shape of somatic evoked potential, none has evaluated the influence on the spatio-temporal pattern of neural activity in detail. It is practically impossible to analyze neural activities spatially, using conventional electrophysiological methods. Applying our multiple-site optical recording technique for measuring membrane potential from multiple-sites with a high time resolution, we compared the spatio-temporal pattern of the evoked activity under two different anesthetic conditions induced by urethane or α-chloralose. The somatic cortical response was evoked by electrical stimulation of the hindlimb, and the optical signals were recorded from the rat sensorimotor cortex stained with a voltage-sensitive dye (RH414). The evoked activity emerged in a restricted area and propagated in a concentric manner. The spatio-temporal pattern of the evoked activity was analyzed using isochrone maps. There were significant differences in the latency and propagation velocity of the evoked activity, as well as the full width at half maximum of optical signal between the two anesthetic conditions. Differences in the amplitude and the slope of the rising phase were not significant.